La esclavitud sofística del alma al cuerpo en el Fedón - Forciniti, Martin (Sapere Aude, 2012)
In this article I analize the metaphor of the master and slave in Plato´s Phaedo, as used to describe the relationship between soul and body. My goal is to determine the role that the sophist plays in the bondage of the soul to the body, considered harmful by the philosophers. In that sense, I identify body´s and soul´s own desires, and the opinions (dóxai) about the good that arise in the soul as a result of pursuing bodily desires. Finally, I develop the way the sophist feeds somatic dóxa itself, wich identifies the good with the pleasant.